Coretax System dan Pajak UMKM di Kabupaten Banyumas - Warsidi, Warsidi (Jurnal Pengabdian Bisnis dan Akuntansi, 2025)
Banyumas Regency, Central Java, holds significant economic potential through various SME sectors, ranging from trade and services to home industries. However, most SME actors still face challenges in understanding and fulfilling tax obligations, particularly regarding the use of the Coretax System and the calculation of the Final Income Tax for SMEs. This community service activity aims to improve tax literacy and practical skills of SME actors through training and mentoring. The methods used include needs assessment, theoretical training, practical assistance, and evaluation using pretests and post-tests. The results show an increase in the average participant score from 65 in the pretest to 80 in the post-test, with an average increase of 15%. Eight out of ten participants experienced significant improvement in understanding and skills. This activity demonstrates that structured mentoring can enhance compliance and capability of SME taxpayers in utilizing the Coretax System and managing the Final Income Tax for SMEs accurately.